PROFIL SELF EFFICACY SISWA CLIMBER TERHADAP PERMASALAHAN MATEMATIKA LEVEL TINGGI BERDASARKAN TAHAPAN POLYA - Ferry Kurnia Putra; Hobri Hobri; Susi Setiawani (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
This research aims to describe about the profile of climber students’ self efficacy to the problem solving skills of high level mathematics problems. It is including form of descriptive research with qualitative approach. The research subjects are 13 climber students in class XI MIPA 8 of SMA Negeri 1 Jember, were tested by Adversity Response Profile (ARP) questionnaire. The method of data collection use a test of problem solving skills of high level mathematics problems, adversity response profile (ARP) questionnaire and interviews. The results of this research showed that the climber students are tend to have high self efficacy and able to by every Polya’s stages.